2015
DOI: 10.1111/jgh.12725
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcome of patients with cirrhosis and refractory ascites treated with transjugular intrahepatic portosystemic shunt insertion

Abstract: TIPS is an effective treatment for cirrhotic refractory ascites. Ascites clearance is dependent on number of TIPS revision, whereas survival is predicted by younger age, complete response, and covered stent use, although era effect likely contributed to improved survival with covered stent use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 36 publications
10
48
0
Order By: Relevance
“…These findings correspond with the results of current literature: in a multicenter, randomized trial including 137 patients, Perarnau et al[12] found that covered stents provided a significant 39% reduction in dysfunction as compared to bare stents [12]. Likewise, Tan et al [25] ascertained that more patients with bare stents developed shunt dysfunction and required TIPS revisions (74.0 vs. 24.1%). In a prospective study including 80 patients, Bureau et al [16] documented similar results after a 2 years follow-up (43.9 vs. 15.0%).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings correspond with the results of current literature: in a multicenter, randomized trial including 137 patients, Perarnau et al[12] found that covered stents provided a significant 39% reduction in dysfunction as compared to bare stents [12]. Likewise, Tan et al [25] ascertained that more patients with bare stents developed shunt dysfunction and required TIPS revisions (74.0 vs. 24.1%). In a prospective study including 80 patients, Bureau et al [16] documented similar results after a 2 years follow-up (43.9 vs. 15.0%).…”
Section: Discussionsupporting
confidence: 80%
“…In a prospective study including 80 patients, Bureau et al [16] documented similar results after a 2 years follow-up (43.9 vs. 15.0%). TIPS dysfunction rates depending on stent type according to current literature are demonstrated in Table 4 [12, 16, 25-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Of note, that in the follow‐up of patients with covered TIPSS, the reintervention rate due to TIPSS dysfunction or hepatic encephalopathy ranges, according to recent reports, from 7% to 42% depending on the duration of follow‐up and technical characteristics of the TIPSS. Moreover, patients with repeat LVP due to RA are regularly seen in out‐patient clinics or, depending on the respective country, even require short hospitalisations for the treatment of the ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the reimbursement of tolvaptan therapy in Japan, dose escalation of spironolactone, loop and thiazide diuretics had been the first-choice strategy for the medical management of patients with refractory ascites, despite its associations with glomerular damage and hyponatremia (3). Although abdominal paracentesis with drainage, cell-free and concentrated ascites reinfusion therapy and trans-jugular intrahepatic portosystemic shunt placement are occasionally used, results suggest that these procedures do not improve overall prognosis (18)(19)(20). Tolvaptan may delay the need for invasive procedures and readmission for patients with refractory ascites.…”
Section: Univariate Analysismentioning
confidence: 99%